Real-time electro-hydraulic trajectory tracking using an optimized sliding mode control design with PID Structure - Ghazali, Rozaimi; Ghani, Muhamad Fadli; Hanaffi, Mohd Saidi; Jaafar, Hazriq Izzuan; Soon, Chong Chee; Has, Zulfatman (2023)
The electro-hydraulic actuator (EHA) tracking control using an approach of sliding mode control with a PID structure denoted as SMCPID is described in this paper. The most optimal SMCPID controller variables had been identified using a particle swarm optimization (PSO) approach, which needed the fewest mathematical interpretations. The closed-loop system with the proposed control is assessed for stability using the stability Lyapunov's theory. Simulation and real-time implementation were used to accumulate the tracking control system's control response in association to assess the trajectory tracking control performance. Using a PCIe-6321 card-equipped EHA workbench, multi-sinusoidal trajectory tracking was implemented in real-time. The proposed controller is superior to the conventional sliding mode controller (SMC) for trajectory tracking control, according to experimental data.